2022
DOI: 10.14218/jerp.2021.00034
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia annua L. and Its Derivatives: Their Antiviral Effects on COVID-19 and Possible Mechanisms

Abstract: COVID-19 is a worldwide pandemic. Currently, there are a few approved effective antiviral drugs against COV-ID-19. Therefore, an effective way to treat an emerging disease is to use existing medicines, which usually have a safety profile. A large number of compounds are produced from traditional medicinal plants and some of them that have antiviral activity could be used as therapeutics, such as Artemisia annua L. Here, we update the information on the therapeutic effects and possible antiviral mechanisms of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Of interest, Wambier and Goren reported that androgens could upregulate the expressions of TMPRSS2 protein and ACE2 receptor [133]. Artemisinin can induce androgen receptor degradation and can disrupt the androgen response [134]; therefore, it might limit the expression of ACE2 and TMPRSS2 in sensitive cells, and thus inhibit SARS-CoV-2 infection [135]. CD147, a transmembrane glycoprotein, can increase the synthesis of matrix metalloproteinases (MMPs) and proinflammatory cytokines [136].…”
Section: Brief Description Of Sars-cov-2 Genome and Possible Targets ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, Wambier and Goren reported that androgens could upregulate the expressions of TMPRSS2 protein and ACE2 receptor [133]. Artemisinin can induce androgen receptor degradation and can disrupt the androgen response [134]; therefore, it might limit the expression of ACE2 and TMPRSS2 in sensitive cells, and thus inhibit SARS-CoV-2 infection [135]. CD147, a transmembrane glycoprotein, can increase the synthesis of matrix metalloproteinases (MMPs) and proinflammatory cytokines [136].…”
Section: Brief Description Of Sars-cov-2 Genome and Possible Targets ...mentioning
confidence: 99%
“…CD147, a transmembrane glycoprotein, can increase the synthesis of matrix metalloproteinases (MMPs) and proinflammatory cytokines [136]. Artemisinin at 20-80 µg/mL inhibited the expression of CD147 [136], suggesting that it might also be effective [135].…”
Section: Brief Description Of Sars-cov-2 Genome and Possible Targets ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The plant extract showed significant activity against the SARS coronavirus that occurred in 2002, and it was selected for its significant inhibitory effect among 200 Chinese medicinal herbs screened for antiviral activities against SARS-CoV ( 23 ). Some studies have also reported the in vitro inhibitory activity of Artemisia annua against SARS-CoV-2 and most of these studies have focused mainly on the artemisinin component and its derivatives ( 24 , 25 ). It is, however, necessary to explore other known bioactive compounds of the plant, including the non-artemisinin components, to fully maximize the anti-SARS-CoV-2 potential of the plant in the development of drugs against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A. annua and its artemisinin component have been found in recent studies to inhibit the enzymatic activity of 3CL pro ( 24 , 25 ). In 2005, the first study indicating A. annua as an anti-SARS-CoV agent was reported.…”
Section: Introductionmentioning
confidence: 99%